Adolescents' health literacy is directly associated with their physical activity but indirectly with their body composition and cardiorespiratory fitness: mediation analysis of the Slovak HBSC study data - Lenka Hnidková; Peter Bakalár; Rastislav Magda; Peter Kolarčik; Jaroslava Kopčáková; Zuzana Boberová (BMC, 2024)
Abstract Background Health literacy is a core public health issue in relation to children and adolescents associated with multiple health behaviours and health outcomes. The aim of the study is to test the direct associations between health literacy, physical activity behaviour, health outcomes of body composition and cardiorespiratory fitness among Slovak adolescents and possible indirect effect of health literacy on health outcomes of body composition and cardiorespiratory fitness mediated by adolescents' physical activity behaviour. Methods Data from the Slovak Health Behaviour in School-aged Children (HBSC) study conducted in 2022 were used. For the purposes of this study, a subsample of the adolescents (n = 508; mean age = 14.50; SD = 0.82; 54.3% boys) which provided HBSC questionnaire data on health literacy, moderate-to-vigorous physical activity and vigorous physical activity and participated in body composition (InBody 230) and cardiorespiratory fitness (20-m shuttle run test) measurements. Data were analysed using linear regression analysis. Results The findings showed that higher health literacy of the adolescents was directly associated with higher frequency of physical activity represented by moderate-to-vigorous physical activity and vigorous physical activity and only with the visceral fat area in the crude model. Furthermore, there was an indirect effect of health literacy on cardiorespiratory fitness and most of the body composition variables (except the Body Mass Index) which was mediated by physical activity of the respondents. Conclusions Health literacy is indirectly associated to body composition and cardiorespiratory fitness through higher frequency of physical activity. It seems that health literacy as cognitive and social competencies need behavioural components to be involved in the proposed causal pathway between health literacy and health outcomes. Our findings may contribute to the process of creating a framework for future health literacy interventions in adolescents.